Mapping the Landscape of Political Transformation: A Bibliometric Analysis via Bibloshine - Adhikari, Kanshi Prasad; Timseena, Bhanu (International Journal of Humanities, Education, and Social Sciences, 2025)
Background: Political transformation plays a critical role in shaping societies, yet there has been limited bibliometric exploration of its research trends. This study seeks to map the intellectual landscape of political transformation by examining key factors such as annual publications, influential sources, and emerging research topics. Methods: A systematic bibliometric approach was applied to analyze political transformation research published between 2014 and 2024. Data were extracted from Scopus, focusing on Open Access, English-language articles and book series within the Social Sciences. Analysis was performed using Biblioshiny to assess publication trends, institutional affiliations, citation patterns, and keyword dynamics. Results: The study identified an upward trend in political transformation publications, with key contributions from European countries and leading academic institutions. Keyword analysis revealed central themes like governance, political economy, and regional shifts. Collaboration networks highlighted increasing international cooperation, and citation analysis pinpointed influential works in the field. Conclusion: This research offers the political transformation field, revealing growing interdisciplinary collaboration and emerging themes. The findings highlight the field’s significant impact on both academia and policy-making.